(untitled) (Papeles, 2025)
This article presents a compilation and systematization of studies, theses and bibliographic material referring to the Reconceptualization Movement (MR) that occurred during 1960 and 1970 in Argentina. The elaboration of this state of the art (not conclusive) emphasizes the main hypotheses that the authors maintain regarding the incidence of MR in the theoretical - methodological and ethical - political shift that the profession is experiencing at the level of training and intervention processes. Published books and postgraduate theses produced since the mid-2000s were mainly addressed, where the following are taken as objects of study: the impacts of the last civic - military, religious and business coup in the social sciences and in the particularity of the TS; the emergence, apogee and crisis of the Reconceptualization Movement and the incidence of said process in the training spaces of Social Work. We propose, then, to map what was produced to place new hypotheses that reconstruct the reconfigurations and expressions of collective professional resistance that took place during and after the last dictatorship in the country.